The Impact of Resident Involvement in Elective Posterior Cervical Fusion - Lee, Nathan J; Kothari, Parth; Kim, Christopher; Leven, Dante M; Skovrlj, Branko; Guzman, Javier Z; Steinberger, Jeremy; Cho, Samuel K (Spine (Philadelphia, Pa. 1976), 2018)
Retrospective study of prospectively collected data OBJECTIVE.: The aim of this study was to assess the impact of resident surgeon involvement on patient outcomes following posterior cervical fusion (PCF) surgery. Recently, there has been a significant uptrend in the number of PCF performed in the United States. Prior studies have investigated patient outcomes after cervical arthrodesis. Despite the heightened concern for patient safety and quality improvement, the data on the safety of resident participation in PCF is sparse. The American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) was examined from 2005 to 2012. Current Procedural Terminology codes were used to query the database for adults (≥18 years) who underwent PCF. Multivariate logistic regression models were employed on data adjusted by propensity scores to determine whether resident involvement was an independent predictor for the outcomes of interest. A total of 448 cases were assessed in NSQIP. Less than half of these cases involved residents (224, 43.1%). Resident involvement was found to be a significant predictor for blood transfusions [odds ratio (OR) = 1.7, confidence interval (CI) = 1.1-2.6, P = 0.010], length of stay of more than 5 days (OR = 1.6, CI = 1.0-2.6, P = 0.040), and operative time more than 4 hours (OR = 3.6, CI = 1.7-7.4, P = 0.0007). Other independent risk factors for prolonged length of stay included age 81 years or older versus 50 years or younger (OR = 4.7, CI = 1.7-12.6, P = 0.016) and diabetes (OR = 2.3, CI = 1.3-4.1, P = 0.006). In addition, multifusion was identified as a significant risk factor for extended operative time (OR = 1.8, CI = 1.1-2.9, P = 0.023). The present study used a large, nationwide sample to assess the impact of resident involvement in PCF. Resident participation was not associated with mortality, but had a minimal association with morbidity. 3.